A validated liquid chromatography‐tandem mass spectroscopy method for the quantification of tolinapant in human plasma. Issue 5 (4th June 2022) - Martins, Vanessa; Wilsher, Nicola; Lin, Song; Oganesian, Aram
Abstract: Tolinapant (ASTX660), a pan‐selective inhibitor of apoptosis protein antagonist with dual cIAP/XIAP activity, was identified as a clinical candidate in preclinical efficacy, pharmacokinetic and safety studies. In order to assess tolinapant in first‐in‐human Phase I/II clinical trials, a validated bioanalytical method was required to determine plasma pharmacokinetics. Tolinapant and d4 ‐tolinapant were extracted from human plasma using liquid‐liquid extraction. Separation chromatography was performed on a Acquity BEH C18 1.7 µM, 50 mm × 2.1 mm i.d. column, using a mobile phase of 0.1% formic acid in water and 0.1% formic acid in acetonitrile. Mass spectrometry detection was performed by positive turbo ion spray ionisation, in multiple reaction monitoring mode. The method was validated according to the US Food and Drug Administration (FDA) guidelines. The method has a quantifiable linear range of 1–500 ng/mL ( r 2  = 0.999). The intra‐ and inter‐day coefficients of variation were < 11.4%. Dilution QC samples agreed with prepared concentrations, with a precision of 1.5% and accuracy of 101%. Tolinapant mean recoveries ranged from 85.1–94.4 % with negligible matrix effects. A highly sensitive and selective LC‐MS/MS bioanalytical method was developed and validated. The method was successfully applied in Phase 1/2 clinical trials to determine the human pharmacokinetic profile of tolinapant.